Respuesta :
Evaluating the given expressions and simplifying the answers, we would have:
1. 6
2. 2
3. -1
4. 0
How do you Evaluate an Expression?
To evaluate an expression, plug in the value of the variable given and simplify.
Thus:
1. 5 - x/3 for x = -3
Substitute x = -3 into the expression
5 - (-3)/3 = 5 - (-1) = 6
2. - 2 + 2x/3 for x = 6
-2 + 2(6)/3
-2 + 4
= 2
3. 2 - 3x/4 for x = 4
2 - 3(4)/4
2 - 3
= -1
4. -3 + x/2 for x = 6
-3 + 6/2
-3 + 3
= 0
Therefore, evaluating the given expressions and simplifying the answers, we would have:
1. 6
2. 2
3. -1
4. 0
Learn more about evaluation of expression on:
https://brainly.com/question/3590570